Analysis of excessive corticosteroid use as an indicator of poor quality of care in patients with inflammatory bowel disease - Mirela Bašić Denjagić; Mirna Alečković-Halilović; Lejla Rakovac-Tupković; Predrag Jovanović; Zlatan Mehmedović; Enver Zerem (Medicinski glasnik, 2024)
Aim: To evaluate the clinical impact of corticosteroids (CS) overuse in inflammatory bowel disease (IBD) patients. Excessive use of CS could delay more efficacious treatment and may indicate poor quality of care. Method: This is a two-phase study that used Steroid Assessment Tool (SAT) to measure corticosteroid exposure in IBD patients. In the first phase data from 211 consecutive ambulatory patients with IBD (91 with ulcerative colitis, 115 with Crohn's disease, and five with unclassified inflammatory bowel disease) were analyzed by SAT. In the second phase, one year after data entry, clinical outcome of patients with cortico-steroids overuse was analysed. Results: Of the 211 IBD patients, 132 (62%) were not on corticosteroids, 45 (22%) were cortico-steroid-dependent and 34 (16%) used corticosteroids appropriately, according to the European Crohn's and Colitis Organization guidelines. In the group of patients with ulcerative colitis, 57 (63%) were not on cortico-steroids, 18 (20%) were corticosteroid-dependent, and 16 (16%) used cortico-steroids appropriate-ly; in the group of patients with Crohn's disease 70 (61%), 27 (23%) and 18 (16%), respectively. Overall, 24 (out of 45; 53%) patients with IBD could avoid the overuse of cortico-steroids if they had a timely change of the treatment, surgery or entered a clinical trial. Conclusion: An excessive corticosteroid use can be recognized on time using the SAT. We have proven that excessive corticosteroid use could be avoided in almost half of cases and thus the overuse of CS may indicate poor quality of care in those patients.
Keywords: audit; quality of health care; steroid use